Pesan Moral Dalam Buku Kelong-Kelongna Tau Mangkasaraka Karya Kembong Daeng - Bagaskara, Muhammad Arsyil; Agussalim, Andi; H, Hajrah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Kelong is one of the regional literary forms that has been present alongside the activities of the Makassar community since ancient times. The book "Kelong-kelongna Tau Mangkasaraka" by Kembong Daeng is one of the kelongs that contains 110 titles filled with various moral messages. This study aims to describe the moral messages found in "Kelong-kelongna Tau Mangkasaraka" by Kembong Daeng. The results of the study show that the moral messages in "Kelong-kelongna Tau Mangkasaraka" by Kembong Daeng consist of (1) moral messages related to the relationship between humans and God, such as urging to acknowledge the oneness of God, acknowledging the existence of Prophet Muhammad as the Messenger of God, the command to establish prayers and fulfill zakat, and performing hajj; (2) moral messages related to the relationship between humans and themselves, including cultivating good attitudes and behaviors, avoiding jealousy, working hard, actively seeking knowledge, and messages to stay away from arrogance and greed; (3) moral messages related to the relationship between humans and others, including messages to respect and be kind to others.